Weight change and mortality: Long‐term results from the trials of hypertension prevention - Cook, Nancy R. (J Clin Hypertens (Greenwich), 2018)
Although weight loss improves blood pressure (BP), its association with mortality remains unclear. In the Trials of Hypertension Prevention (TOHP), individuals aged 30‐54 years with high normal BP were randomized to weight loss, usual care or other intervention over 18 months (TOHP I) or 3‐4 years (TOHP II), with average 23‐year mortality follow‐up. We examined mortality and (a) randomized weight loss and (b) observed weight change among all with high baseline weight. Among 2964 randomized participants, 227 deaths occurred, with no intervention difference (hazard ratio (HR) = 0.97, 95% confidence interval (CI) = 0.75‐1.26, P = 0.84). Among 3828 high‐weight participants, weight change was directly related to mortality (HR = 1.14 per 5% change, 95% CI = 1.02‐1.28, P = 0.019). During the trial 15% lost >5% (HR = 0.82), 29% lost 0‐<=5% (HR = 0.94), 41% gained 0‐<5% (reference), and 16% gained >5% (HR = 1.29) (P‐trend = 0.046). This is consistent with a long‐term beneficial effect of presumed intentional weight loss on mortality.